Gauging the COVID-19 on Academic Stress on Tertiary Level Female Students on the eve of COVID-19 (KASBIT Business Journal, 2022)
It has been observed that COVID-19 has increased stress which causes psychological harm. The situation is vibrant even among students who have to attend classes during stressful times. Although university level students have to bear more stress due to the level and complexity of their studies. Therefore, literature is also indicating the stress and impact of the stress on level students from different countries. Although some of the studies have also indicated the tertiary positive impact of online classes. Therefore, this study aims to clarify the impact of COVID-19 on tertiary-level students from Pakistan amid COVID-19. Previous studies were majorly based on medical students although in Pakistan most of the tertiary level students are associated with management science. Therefore, the study focuses extensively on female students pursuing tertiary level education in private sector universities of Karachi. The data has been collected through a closed-ended questionnaire through convenience sampling and the sampling size was 400 female students pursuing their bachelor’s degrees in management sciences. Results indicated that COVID-19 has increased academic stress on tertiary-level female students.
Keywords: COVID-19; Perceived Level of Stress; Online Classes; Tertiary Level Education